SISTEM OTOMATISASI DAN KENDALI JARAK JAUH LAMPU SMART HOUSE BERBASIS NODEMCU ESP8266 - Ningrum, Febri Sintia; Triadyaksa, Pandji (BERKALA FISIKA, 2020)
Internet of Things (IoT) is a concept that aims to expand the benefits of continuously connected internet connectivity. This research aims to utilize IoT on home remote control and automates systems that can be operated with a smart phone application via an internet connection (WiFi). This system used the NodeMCU ESP8266 module as a microcontroller, the light emitting diode (LDR)  sensor  as  an  automation  controller  for  lighting  the  environment  according  to environmental conditions, and the Blynk smartphone application as a remote controller. The process of controlling the lights can be done specifically on certain lights and can be controlled by  the  changes  of  environmental  light  in  the  morning  and  evening.  The  results  showed  that when the LDR sensor was poorly lit, the lamp would be ON and otherwise the lamp would be OFF when the LDR receives more light intensity. In addition, the Blynk application is able to control the lights when connected with internet and tested, in this research, up to 2.7 km. It can be concluded that as long as the system is connected to the WiFi in a stable and continuous manner,  then  this  control  system  can  perform  the  task  of  turning  on  and  off  the  lights independently when the owner is not at home.Keywords: Internet of Things (IoT), Blynk, LDR, Smart House, NodeMCU ESP6288